Pengembangan Sistem Informasi Lembaga Pengkajian dan Konsultan Bantuan Hukum (LPKBH) Menggunakan Zachman Framework (Studi Pada LPKBH Al-Baihaqy) - Irfan Asnawi; Yusi Tyroni Mursityo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Institute of Assessment and Legal Aid Consultant (IALAC) Al-Baihaqy is one of the legal aid agencies in Indonesia located in Surabaya Based on the results of the interview, there are some problems that are being faced by LPKBH Al-Baihaqy, such as the difficulty in finding clients when many people who have problems in law and client does not make a payment at the time of consultation. From these problems, it is necessary to analyze the current business processes and designing an application that can help IALAC Al-Baihaqy in finding clients and solve problems the client does not pay when consulted. In this research, business process analysis using Bussiness Proccess Improvement (BPI) method and designing application using zachman framework. Zachman framework is a logical structure to clarify and organize significant Enterprise descriptive representations of Enterprise management and Enterprise system development, manual systems and automated systems. This research results are modeling of current business processes and proposals, system design based on analysis using zachman framework, and system prototypes. In addition, a business process simulation using Bizagi Modeler is performed. The simulation is done up to level two, ie process validation and time analysis. System prototype testing uses black-box testing and white-box testing.